A large-pore ceramic grinding wheel and a preparation method thereof

CN122956374APending Publication Date: 2026-10-23HUTTON ABRASIVES (WUXI) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611293401.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,该专利仅单一采用表面改性核桃壳作为造孔组分,未复配多类差异化热解造孔原料与功能性辅助造孔填料,无法实现宽区间气孔精准调控,且未改良陶瓷结合剂体系,高气孔状态下砂轮抗弯强度衰减明显,同时缺少分段负压动态供氧烧结配套工艺,仍存在窑内瞬时产气聚集、批量产品气孔离散度偏大、烧成能耗偏高的缺陷

Benefits of technology

(1)本发明公开的大气孔陶瓷砂轮及其制备方法,通过打破传统单一造孔剂造孔孔径单一、气孔分布不均的技术瓶颈,采用差异化表面改性的核桃壳粉、PMMA微球、HDPE三元环保造孔剂复配硅烷改性酚醛空心微球的错峰热解造孔体系,搭配铋盐基低温陶瓷结合剂与含柠檬酸钠的丙烯酸-PVA一体化树脂粘结体系的多元组分协同适配,有效解决了传统大气孔砂轮气孔率可调范围窄、孔隙结构杂乱的行业难题,取得了砂轮气孔率宽范围精准可调、孔隙结构规整可控的核心技术效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a large-pore ceramic grinding wheel and a preparation method thereof, relates to the technical field of ceramic grinding wheels, and discloses the following technical scheme: the grinding wheel raw material comprises abrasive, low-temperature ceramic bonding agent, surface grading modified ternary environment-friendly pore-forming agent, composite modified resin temporary bonding system, dispersing defoaming agent and auxiliary pore-forming component; the ternary environment-friendly pore-forming agent is compounded according to a specific mass ratio of citric acid activated walnut shell powder, plasma etching PMMA microspheres and maleic anhydride grafted HDPE. During preparation, the pore-forming agent is pretreated, gradient mixing is carried out, disc step-by-step pressure forming is carried out, segmented temperature and humidity control drying is carried out, and then low-temperature pre-insulation, staggered pyrolysis, ceramic sintering and ladder slow cooling are sequentially completed through oxygen pressure linkage negative pressure push plate kiln. According to the application, the ternary grading pore-forming system and the sintering process are synergistically controlled, a multi-level pore structure with uniform pore distribution can be obtained, the high apparent porosity is ensured, the bending strength and blasting safety margin of the grinding wheel are improved, the size stability is good, and the application is suitable for large-pore ceramic grinding wheel manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic grinding wheel technology, and in particular to a ceramic grinding wheel with large porosity and its preparation method. Background Technology

[0002] With the rapid development of modern machining industry, the demand for processing high-hardness rolls such as high-chromium steel and high-speed steel, as well as precision ceramic electronic components, is increasing. In the grinding of these high-hardness materials, traditional ceramic grinding wheels often suffer from insufficient cutting force and difficulty in chip removal, easily causing burns and scratches on the workpiece surface during processing, severely affecting the surface accuracy and yield. It is under these circumstances that large-pore ceramic grinding wheels have emerged, attracting widespread attention in the industry.

[0003] Large-pore ceramic grinding wheels are core grinding tools in the field of precision grinding. Their interconnected internal pore structure enables chip removal and heat dissipation, making them widely used in the precision machining of high-hardness rolls, linear guides, and ceramic electronic components. They effectively reduce the temperature in the grinding zone, preventing workpiece burns. Traditional large-pore ceramic grinding wheels often use refined naphthalene and sulfur as pore-forming agents. These agents volatilize during the drying and sintering stages, producing toxic and harmful gases that endanger the health of production personnel and the workshop environment. Furthermore, the rapid volatilization rate weakens the bonding agent's grip on the abrasive, leading to bond bridge breakage. This results in significantly lower rotational strength compared to ordinary ceramic grinding wheels of the same hardness, and a drastically shortened service life.

[0004] Some improved solutions use walnut shells and dextrin as pore-forming agents and temporary binders in an attempt to replace toxic pore-forming agents. However, under the low-density, high-porosity formulation system, the strength of the grinding wheel green body is insufficient, and morphological defects such as edge and corner damage are prone to occur during production and transportation. Furthermore, the volatilization rates of the pore-forming agent and binder are inconsistent during the sintering stage, and stress concentration is prone to occur inside the green body, leading to cracks. The industry average product qualification rate is low.

[0005] On the other hand, existing sintering processes for atmospheric porous ceramic grinding wheels employ a constant heating rate and atmospheric pressure sintering mode, failing to differentiate temperature and pressure control based on the decomposition characteristics of different temperature ranges. In the low-temperature pore-forming decomposition section, the heating rate is too rapid, preventing the gas from slowly seeping out and creating internal pressure within the blank, resulting in microcracks. In the medium- and high-temperature ceramic binder sintering section, the lack of negative pressure assistance prevents the complete oxidation and burning off of residual carbon particles, reducing the wheel's bonding strength and grinding stability. The uniform heating rate throughout the process leads to rapid cracking in the low-temperature pore-forming section and slow heating in the high-temperature sintering section, prolonging kiln occupancy and resulting in high energy consumption. The porosity of grinding wheels prepared by conventional atmospheric pressure processes is extremely poor, with significant differences in porosity at different locations on the same wheel, making it impossible to guarantee product consistency and hindering mass production for precision heavy-duty grinding.

[0006] To address the aforementioned issues, invention patent document CN112677059A discloses a low-density, high-porosity ceramic grinding wheel, comprising 100 parts abrasive; 10-30 parts ceramic binder; 5-15 parts pore-forming agent; and 2-5 parts resin binder. The resin binder is a mixture of resin liquid and diluent, with a resin liquid to diluent ratio of 1:1 to 1:4. This invention provides a low-density, high-porosity ceramic grinding wheel that uses a modified resin binder, replacing the temporary binder and wetting agent in the prior art. This improves the strength of the grinding wheel green body, reduces the rate of morphological defects during production, and increases the product quality pass rate. Simultaneously, the surface-treated walnut shell reduces the risk of uneven volatilization during drying and sintering, preventing defects such as cracks in the ceramic grinding wheel. Furthermore, the pressed grinding wheel green body can be directly cured, shortening the drying time and improving production efficiency. However, this patent only uses surface-modified walnut shells as the pore-forming component, without compounding multiple types of differentiated pyrolysis pore-forming raw materials and functional auxiliary pore-forming fillers. It cannot achieve precise control of pores over a wide range, and the ceramic binder system has not been improved. Under high porosity conditions, the bending strength of the grinding wheel is significantly reduced. At the same time, it lacks a segmented negative pressure dynamic oxygen supply sintering process, and still suffers from defects such as instantaneous gas accumulation in the kiln, large pore dispersion of batch products, and high firing energy consumption. Summary of the Invention

[0007] To overcome the shortcomings of the above-mentioned technologies, this invention provides a large-porosity ceramic grinding wheel and its preparation method. It involves differentiated surface modification of walnut shells, PMMA, and HDPE, combined with silane-modified phenolic hollow microspheres to form a staggered pyrolysis pore-forming system. This system is then combined with a bismuth-based low-temperature ceramic binder and an integrated acrylic-PVA resin bonding system containing sodium citrate. The process includes a complete set of steps: pore-forming agent sieving pretreatment, gradient mixing, rotary molding, segmented temperature and humidity controlled drying, four-stage oxygen pressure-linked negative pressure sintering, low-temperature pre-heating, and stepped slow cooling. This achieves precise adjustment of porosity over a wide range. The product exhibits excellent bending strength and self-sharpening properties under high porosity conditions, significantly reducing firing scrap rate and fuel consumption, and eliminating the emission of toxic naphthalene and benzene-based waste gases throughout the entire process.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: a large-pore ceramic grinding wheel, made from the following raw materials in parts by weight: 100 parts abrasive, 20-28 parts low-temperature ceramic binder, 10-22 parts surface-graded modified ternary environmentally friendly pore-forming agent, 4-8 parts composite modified resin integrated temporary bonding system, 0.1-0.3 parts dispersant and defoamer, and 0.1-0.3 parts auxiliary pore-forming components; the surface-graded modified ternary environmentally friendly pore-forming agent is compounded from citric acid activated walnut shell powder, plasma-etched PMMA microspheres, and maleic anhydride grafted HDPE in a mass ratio of 1:2:(0.8-1.2).

[0009] Preferably, the abrasive is at least one of white fused alumina, brown fused alumina, and green silicon carbide.

[0010] Preferably, the white fused alumina has a particle size of F80; the brown fused alumina has a particle size of F100; and the green silicon carbide has a particle size of F120.

[0011] Preferably, the low-temperature ceramic binder comprises the following components by weight: 70-74 parts of bismuth-based low-temperature glass powder, 14-16 parts of mullite short whiskers, 3-5 parts of rare earth powder, 4-6 parts of lithium hexafluorosilicate powder, and 3-5 parts of nano-zirconia powder; the nano-zirconia powder is pre-treated by wet ultrasonic dispersion to inhibit powder agglomeration; the mullite short whiskers have an aspect ratio of 20-60 to avoid defects caused by excessively long whiskers entanglement and agglomeration.

[0012] Preferably, the bismuth-based low-temperature glass powder is bismuthate-based glass powder B-5016; the mullite short whiskers have a diameter of 0.2-3 micrometers; the rare earth powder is HX-301 type polishing powder; the D50 of the lithium hexafluorosilicate powder is 2-8 μm; and the average particle size of the nano-zirconia powder is 30-50 nm.

[0013] Preferably, the preparation method of the citric acid activated walnut shell powder includes the following steps: crushing and sieving raw walnut shells to obtain 60-100 mesh powder, washing with clean water and drying at 78-82℃, completely immersing the powder in a 5wt% citric acid-ethanol mixture prepared by anhydrous ethanol and food-grade citric acid at a solid-liquid mass ratio of 1:6, stirring and soaking in a sealed water bath at 78-82℃ for 1.8-2.2 hours, then rinsing repeatedly with anhydrous ethanol to remove free citric acid, drying with hot air at 98-102℃, and sieving to remove lumps to obtain the finished product.

[0014] Preferably, the method for preparing the plasma-etched PMMA microspheres includes the following steps: PMMA microspheres are monolayered and laid flat on a low-temperature plasma cleaning substrate under normal pressure. Etching is performed twice using a helium-oxygen mixed gas source with a volume ratio of 1:1 and a 150W radio frequency power, with each etching session lasting 5 minutes, followed by a 10-minute ventilated resting period in between, for a total processing time of 10 minutes. After etching, the microspheres are stored at room temperature under ventilation for 30 minutes in a sealed container away from light. The PMMA microspheres have the product number EPRUI-CPA-1500H and are provided by Shanghai EPRUI Biotechnology Co., Ltd.

[0015] Preferably, the maleic anhydride-grafted HDPE is FUSABOND. TM E158 maleic anhydride-grafted HDPE.

[0016] Preferably, the composite modified resin integrated temporary bonding system comprises the following components by mass percentage: 21-23% Illex VISCOPOL 3324 waterborne acrylic resin, 9-11% Kuraray PVA-217 polyvinyl alcohol, 2-4% glycerol, 0.2-0.5% sodium citrate, and the balance being deionized water.

[0017] Preferably, the dispersing defoamer is Dow Corning defoamer DOWSIL DC-65.

[0018] Preferably, the auxiliary pore-forming component is a compound of BJO-0930 phenolic hollow microspheres and silane coupling agent KH550 in a mass ratio of 100:(3-5).

[0019] Another object of the present invention is to provide a method for preparing the aforementioned atmospheric porous ceramic grinding wheel, comprising the following steps: S1. Pretreatment of pore-forming agent by sieving: Citric acid activated walnut shell powder, plasma etched PMMA microspheres, and maleic anhydride grafted HDPE are mixed according to the formula, and large agglomerated particles are removed by passing through an 80-mesh vibrating screen. Then, it is blended with auxiliary pore-forming components to obtain surface graded modified ternary environmentally friendly pore-forming premix. S2. Gradient mixing: First, put the abrasive into a planetary mixer and premix at low speed for 2-3 minutes. Then, add the dispersant and defoamer and half of the amount of the composite modified resin integrated temporary binder system, and stir for 5-7 minutes to make the surface of the abrasive uniformly coated with a resin liquid film. Next, add the low-temperature ceramic binder powder and stir at high speed for 8-12 minutes. Finally, add the pore-forming premix obtained in step S1 and the remaining composite modified resin integrated temporary binder system, and mix at low speed for 4-6 minutes to obtain a uniform blank. S3. Rotary molding: The blank is put into a rotary molding equipment and a step-by-step pressurization process is adopted. First, the pre-pressure is applied at 0.8-1.2MPa and held for 15-25s to release the air. Then, the pressure is increased to 3.5-4.5MPa and held for 40-60s. The blank is demolded to obtain the grinding wheel blank. S4. Segmented temperature and humidity controlled drying: Place the green blank into a closed humidity-controlled drying kiln and execute a four-stage drying process; S5. Four-stage oxygen pressure linkage negative pressure sintering: The dried green body is placed in a negative pressure pusher kiln and the low temperature preheating, staggered pyrolysis, ceramic sintering and stepped slow cooling processes are performed in sequence. The kiln is equipped with an oxygen probe and a negative pressure detection module to realize the interlocking control of oxygen partial pressure and negative pressure, so as to obtain a ceramic grinding wheel with large porosity.

[0020] Preferably, the four-stage drying process in step S4 is as follows: the first stage is at a temperature of 40-45℃ and a relative humidity of 75-80%, and is held for 8-10 hours; the second stage is at a temperature of 55-60℃ and a relative humidity of 60-65%, and is held for 10-12 hours; the third stage is at a temperature of 70-75℃ and a relative humidity of 40-45%, and is held for 6-8 hours; the fourth stage is at a temperature of 90-95℃, with exhaust ventilation in the kiln turned on and no humidity control, and is held for 4-6 hours. After drying, the moisture content of the green body is ≤0.3wt%.

[0021] Preferably, the low-temperature pre-heating in step S5 specifically involves: drawing a negative pressure inside the kiln to -0.04~-0.06MPa, raising the temperature to 220-240℃ at a rate of 1.2-1.5℃ / min, and holding the temperature for 2.5-3.5h to remove residual resin and moisture from the green body; Preferably, the staggered pyrolysis in step S5 specifically involves: maintaining a negative pressure of -0.03 to -0.05 MPa, and controlling the oxygen partial pressure and heating rate in the kiln in four stages; the first stage temperature is 240-340℃, the heating rate is 0.7-0.9℃ / min, and the oxygen partial pressure is 8-10%, completing the pyrolysis of walnut shell powder; the second stage temperature is 340-420℃, the heating rate is 0.5-0.7℃ / min, and the oxygen partial pressure is 12-15%, completing the pyrolysis of HDPE. Thermal decomposition; the third stage temperature is 420-510℃, the heating rate is 0.4-0.6℃ / min, and the oxygen partial pressure is 15-18%, completing the pyrolysis and gasification of PMMA microspheres; when the negative pressure is lower than the -0.03MPa threshold, the heating rate is automatically reduced to suppress instantaneous gas generation and bubbling defects in the green body; the fourth stage temperature is 510-580℃, the heating rate is 1.0-1.2℃ / min, and the oxygen partial pressure is 5-7%, discharging the residual carbonaceous material from the decomposition of the pore-forming agent.

[0022] Preferably, the ceramic sintering in step S5 specifically involves: heating to 780-820℃ at a rate of 1.4-1.6℃ / min, adjusting the kiln to a slight negative pressure of -0.01~-0.02MPa, and holding the temperature for 2-3 hours.

[0023] Preferably, the stepped slow cooling in step S5 specifically involves: first, cooling to 620-640℃ at a rate of 1.8-2.2℃ / min and holding for 1-1.5 hours; then cooling to 420-440℃ at a rate of 1.2-1.5℃ / min and holding for 1.5-2 hours; and finally, naturally cooling to below 120℃ at a rate of ≤0.8℃ / min before exiting the kiln.

[0024] Due to the application of the above technical solution, the present invention has the following beneficial effects: (1) The atmospheric porous ceramic grinding wheel and its preparation method disclosed in this invention break through the technical bottleneck of single pore size and uneven pore distribution of traditional single pore-forming agent. It adopts a staggered pyrolysis pore-forming system of differentiated surface modified walnut shell powder, PMMA microspheres, HDPE ternary environmentally friendly pore-forming agent compounded with silane modified phenolic hollow microspheres, and a multi-component synergistic adaptation of bismuth salt-based low-temperature ceramic binder and acrylic-PVA integrated resin bonding system containing sodium citrate. It effectively solves the industry problem of narrow adjustable porosity and disordered pore structure of traditional atmospheric porous grinding wheels, and achieves the core technical effect of wide-range precise adjustment of grinding wheel porosity and regular and controllable pore structure.

[0025] (2) The atmospheric porous ceramic grinding wheel and its preparation method disclosed in this invention achieve the compatibility and adaptation between the atmospheric porous structure and the mechanical properties of the grinding wheel by means of the reinforcing and toughening effect of the low-temperature ceramic binder composed of bismuth-based low-temperature glass powder, mullite short whiskers, nano-zirconia, etc., combined with the uniform coating and bonding effect of the acrylic-PVA integrated resin bonding system. This results in a significant improvement in the bending strength and structural stability of the grinding wheel under high porosity conditions, and a significant optimization of the grinding self-sharpening property.

[0026] (3) The atmospheric porous ceramic grinding wheel and its preparation method disclosed in this invention, through the pre-processing of pore-forming agent screening, gradient mixing, and step-by-step pressure molding on a rotary table, and matched with the full-process linkage control of the integrated set of sintering processes of segmented temperature and humidity control drying, four-stage oxygen pressure linkage negative pressure sintering, low temperature pre-heating and step-by-step slow cooling, achieves all-round control of raw material mixing uniformity, green body forming density and sintering process stability, and achieves the technical effect of significantly reducing the grinding wheel firing scrap rate, significantly improving the product qualification rate, and effectively reducing production energy consumption.

[0027] (4) The atmospheric porous ceramic grinding wheel and its preparation method disclosed in this invention adopts a plant-based, high-molecular environmentally friendly modified pore-forming agent and water-based composite resin bonding system throughout the process to replace the traditional naphthalene-based and benzene-based pore-forming and bonding raw materials. Combined with the negative pressure closed sintering waste gas collection and treatment working condition, the technical effect of no naphthalene and benzene toxic waste gas emissions throughout the production process and green and environmentally friendly production process is achieved.

[0028] (5) The large-pore ceramic grinding wheel and its preparation method disclosed in this invention achieve a highly synergistic coupling effect of multi-level pore-forming components by limiting the optimal compounding ratio of ternary modified pore-forming agent 1:2:(0.8-1.2) and combining it with 0.1-0.3 parts of silane-modified phenolic hollow microspheres as auxiliary pore-forming components. The pyrolysis temperature range of citric acid activated walnut shell powder is relatively high, which is responsible for constructing large-diameter interconnected pores in the grinding wheel matrix, ensuring grinding chip removal and heat dissipation channels. The pyrolysis range of plasma-etched PMMA microspheres is in the middle. Relying on the rough interface after etching to improve the bonding force with the binder, a uniform mesoporous structure is stably generated, which makes up for the mechanical attenuation problem caused by the macroporous structure. The pyrolysis temperature of maleic anhydride grafted HDPE is relatively low, which can be used at the pore boundary. This system forms a fine microporous structure and optimizes the distribution of pore layers. The three components undergo staggered pyrolysis without interference and complement each other in forming the pores. The trace amount of silane-modified phenolic hollow microspheres, which are auxiliary pore-forming components, can accurately fill the gaps between primary and secondary pores, playing multiple roles such as pore bridging, interface modification, and pore formation assistance. It effectively improves the compatibility between organic pore-forming components and inorganic ceramic binders, and inhibits pore-forming agent agglomeration, pyrolysis collapse, and closed-pore defects. Compared with single pore-forming agents, unmodified pore-forming compound systems, and no auxiliary pore-forming components, this main-auxiliary synergistic pore-forming system can significantly broaden the pore control range and improve pore uniformity and connectivity without reducing the strength of the grinding wheel matrix. This achieves a simultaneous improvement in high porosity, high structural strength, and excellent self-sharpening performance of the grinding wheel. Detailed Implementation

[0029] The following description is intended to disclose the invention and enable those skilled in the art to implement it. The preferred embodiments described below are merely examples, and other obvious variations will occur to those skilled in the art. Example 1

[0030] A ceramic grinding wheel with large pores is made from the following raw materials in parts by weight: 100 parts abrasive, 20 parts low-temperature ceramic binder, 10 parts surface-graded modified ternary environmentally friendly pore-forming agent, 4 parts composite modified resin integrated temporary bonding system, 0.1 parts dispersant and defoamer, and 0.1 parts auxiliary pore-forming component; the surface-graded modified ternary environmentally friendly pore-forming agent is compounded from citric acid activated walnut shell powder, plasma-etched PMMA microspheres, and maleic anhydride grafted HDPE in a mass ratio of 1:2:0.8.

[0031] The abrasive is white fused alumina; the particle size of the white fused alumina is F80; the low-temperature ceramic binder comprises the following components by weight: 70 parts bismuth-based low-temperature glass powder, 14 parts mullite short whiskers, 3 parts rare earth powder, 4 parts lithium hexafluorosilicate powder, and 3 parts nano-zirconia powder; the nano-zirconia powder is pre-treated by wet ultrasonic dispersion to inhibit powder agglomeration; the mullite short whiskers have an aspect ratio of 20 to avoid defects caused by excessively long whiskers entanglement and agglomeration; the bismuth-based low-temperature glass powder is bismuthate-based glass powder B-5016; the diameter of the mullite short whiskers is 0.2 micrometers; the rare earth powder is HX-301 type polishing powder; the D50 of the lithium hexafluorosilicate powder is 2 μm; and the average particle size of the nano-zirconia powder is 30 nm.

[0032] The preparation method of the citric acid activated walnut shell powder includes the following steps: crushing and sieving raw walnut shells to obtain 60-mesh powder, washing with water and drying at 78°C, completely immersing the powder in a 5wt% citric acid-ethanol mixture prepared by anhydrous ethanol and food-grade citric acid at a solid-liquid mass ratio of 1:6, stirring and soaking in a sealed water bath at 78°C for 1.8 hours, then rinsing repeatedly with anhydrous ethanol to remove free citric acid, drying with hot air at 98°C, and sieving to remove lumps to obtain the finished product.

[0033] The method for preparing the plasma-etched PMMA microspheres includes the following steps: PMMA microspheres are monolayered and laid flat on a low-temperature plasma cleaning substrate under normal pressure. Etching is performed twice using a 1:1 helium-oxygen mixed gas source and 150W RF power, each etching lasting 5 minutes, with a 10-minute interval between etching and ventilation, for a total processing time of 10 minutes. After etching, the microspheres are stored at room temperature under ventilation for 30 minutes in a sealed container away from light. The PMMA microspheres are of catalog number EPRUI-CPA-1500H and are provided by Shanghai Yipurui Biotechnology Co., Ltd. The maleic anhydride-grafted HDPE is FUSABOND. TM E158 maleic anhydride-grafted HDPE.

[0034] The composite modified resin integrated temporary bonding system comprises the following components by mass percentage: 21% Illnex VISCOPOL 3324 waterborne acrylic resin, 9% Kuraray PVA-217 polyvinyl alcohol, 2% glycerol, 0.2% sodium citrate, and the balance being deionized water; the dispersing defoamer is Dow Corning defoamer DOWSIL DC-65; and the auxiliary pore-forming component is BJO-0930 phenolic hollow microspheres and silane coupling agent KH550 compounded in a mass ratio of 100:3.

[0035] A method for preparing the aforementioned porous ceramic grinding wheel includes the following steps: S1. Pretreatment of pore-forming agent by sieving: Citric acid activated walnut shell powder, plasma etched PMMA microspheres, and maleic anhydride grafted HDPE are mixed according to the formula, and large agglomerated particles are removed by passing through an 80-mesh vibrating screen. Then, it is blended with auxiliary pore-forming components to obtain surface graded modified ternary environmentally friendly pore-forming premix. S2. Gradient mixing: First, put the abrasive into a planetary mixer and premix at low speed for 2 minutes. Then, add the dispersant and defoamer and half of the amount of the composite modified resin integrated temporary bonding system, and stir for 5 minutes to make the surface of the abrasive uniformly coated with a resin liquid film. Then, add the low-temperature ceramic binder powder and stir at high speed for 8 minutes. Finally, add the pore-forming premix obtained in step S1 and the remaining composite modified resin integrated temporary bonding system, and mix at low speed for 4 minutes to obtain a uniform blank. S3. Rotary molding: The blank is put into a rotary molding equipment and a step-by-step pressurization process is adopted. First, the pre-pressure is applied at 0.8MPa and held for 15s to release the air, and then the pressure is increased to 3.5MPa and held for 40s. The blank is then demolded to obtain the grinding wheel blank. S4. Segmented temperature and humidity controlled drying: Place the green blank of the grinding wheel into a closed humidity-controlled drying kiln and execute a four-stage drying process; S5. Four-stage oxygen pressure linkage negative pressure sintering: The dried green body is placed in a negative pressure pusher kiln and the low temperature preheating, staggered pyrolysis, ceramic sintering and stepped slow cooling processes are performed in sequence. The kiln is equipped with an oxygen probe and a negative pressure detection module to realize the interlocking control of oxygen partial pressure and negative pressure, so as to obtain a ceramic grinding wheel with large porosity.

[0036] The four-stage drying process in step S4 is as follows: the first stage is at a temperature of 40℃ and a relative humidity of 75%, held for 8 hours; the second stage is at a temperature of 55℃ and a relative humidity of 60%, held for 10 hours; the third stage is at a temperature of 70℃ and a relative humidity of 40%, held for 6 hours; the fourth stage is at a temperature of 90℃, with exhaust ventilation in the kiln turned on and no humidity control, held for 4 hours, and the moisture content of the green body after drying is ≤0.3wt%; the low-temperature pre-heating process in step S5 is as follows: the negative pressure in the kiln is reduced to -0.04MPa, the temperature is increased to 220℃ at a rate of 1.2℃ / min, and held for 2.5 hours to remove residual resin and moisture from the green body.

[0037] The staggered pyrolysis described in step S5 is as follows: maintaining a negative pressure of -0.03 MPa, the oxygen partial pressure and heating rate in the kiln are controlled in four stages; the first stage temperature is 240℃, the heating rate is 0.7℃ / min, and the oxygen partial pressure is 8%, completing the pyrolysis of walnut shell powder; the second stage temperature is 340℃, the heating rate is 0.5℃ / min, and the oxygen partial pressure is 12%, completing the thermal decomposition of HDPE; the third stage temperature is 420℃, the heating rate is 0.4℃ / min, and the oxygen partial pressure is 15%, completing the pyrolysis and gasification of PMMA microspheres; when the negative pressure is lower than the -0.03 MPa threshold, the heating rate is automatically reduced to suppress instantaneous gas generation and bubbling defects in the green body; the fourth stage temperature is 510℃, the heating rate is 1.0℃ / min, and the oxygen partial pressure is 5%, discharging the pore-forming agent to decompose residual carbon.

[0038] The ceramic sintering described in step S5 is as follows: the temperature is increased to 780℃ at a rate of 1.4℃ / min, the pressure inside the kiln is adjusted to a slight negative pressure of -0.01MPa, and the temperature is held for 2 hours. The stepped slow cooling described in step S5 is as follows: first, the temperature is decreased to 620℃ at a rate of 1.8℃ / min and held for 1 hour; then, the temperature is decreased to 420℃ at a rate of 1.2℃ / min and held for 1.5 hours; finally, the temperature is naturally decreased to below 120℃ at a rate of ≤0.8℃ / min before the ceramic is removed from the kiln.

[0039] Example 2

[0040] A type of porous ceramic grinding wheel is made from the following raw materials in parts by weight: 100 parts abrasive, 23 parts low-temperature ceramic binder, 13 parts surface-graded modified ternary environmentally friendly pore-forming agent, 5 parts composite modified resin integrated temporary bonding system, 0.15 parts dispersant and defoamer, and 0.15 parts auxiliary pore-forming component; the surface-graded modified ternary environmentally friendly pore-forming agent is compounded from citric acid activated walnut shell powder, plasma-etched PMMA microspheres, and maleic anhydride grafted HDPE in a mass ratio of 1:2:0.9.

[0041] The abrasive is brown fused alumina; the particle size of the brown fused alumina is F100; the low-temperature ceramic binder comprises the following components by weight: 72 parts of bismuth-based low-temperature glass powder, 14.5 parts of mullite short whiskers, 3.5 parts of rare earth powder, 4.5 parts of lithium hexafluorosilicate powder, and 3.5 parts of nano-zirconia powder; the nano-zirconia powder is pre-treated by wet ultrasonic dispersion to inhibit powder agglomeration; the mullite short whiskers have an aspect ratio of 30 to avoid defects caused by excessively long whiskers entanglement and agglomeration; the bismuth-based low-temperature glass powder is bismuthate-based glass powder B-5016; the diameter of the mullite short whiskers is 1 micrometer; the rare earth powder is HX-301 type polishing powder; the D50 of the lithium hexafluorosilicate powder is 4 μm; and the average particle size of the nano-zirconia powder is 35 nm.

[0042] The preparation method of the citric acid activated walnut shell powder includes the following steps: crushing and sieving raw walnut shells to obtain 70-mesh powder, washing with water and drying at 79°C, completely immersing the powder in a 5wt% citric acid-ethanol mixture prepared by anhydrous ethanol and food-grade citric acid at a solid-liquid mass ratio of 1:6, stirring and soaking in a sealed water bath at 79°C for 1.9 hours, then rinsing repeatedly with anhydrous ethanol to remove free citric acid, drying with hot air at 99°C, and sieving to remove lumps to obtain the finished product.

[0043] The method for preparing the plasma-etched PMMA microspheres includes the following steps: PMMA microspheres are monolayered and laid flat on a low-temperature plasma cleaning substrate under normal pressure. Etching is performed twice using a 1:1 helium-oxygen mixed gas source and 150W RF power, each etching lasting 5 minutes, with a 10-minute interval between etching and ventilation, for a total processing time of 10 minutes. After etching, the microspheres are stored at room temperature under ventilation for 30 minutes in a sealed container away from light. The PMMA microspheres are of catalog number EPRUI-CPA-1500H and are provided by Shanghai Yipurui Biotechnology Co., Ltd. The maleic anhydride-grafted HDPE is FUSABOND. TM E158 maleic anhydride-grafted HDPE.

[0044] The composite modified resin integrated temporary bonding system comprises the following components by mass percentage: 21.5% Illex VISCOPOL 3324 waterborne acrylic resin, 9.5% Kuraray PVA-217 polyvinyl alcohol, 2.5% glycerin, 0.3% sodium citrate, and the balance being deionized water; the dispersing defoamer is Dow Corning defoamer DOWSIL DC-65; and the auxiliary pore-forming component is BJO-0930 phenolic hollow microspheres and silane coupling agent KH550 compounded in a mass ratio of 100:3.5.

[0045] A method for preparing the aforementioned porous ceramic grinding wheel includes the following steps: S1. Pretreatment of pore-forming agent by sieving: Citric acid activated walnut shell powder, plasma etched PMMA microspheres, and maleic anhydride grafted HDPE are mixed according to the formula, and large agglomerated particles are removed by passing through an 80-mesh vibrating screen. Then, it is blended with auxiliary pore-forming components to obtain surface graded modified ternary environmentally friendly pore-forming premix. S2. Gradient mixing: First, put the abrasive into a planetary mixer and premix at low speed for 2.3 min. Then, add the dispersant and defoamer and half of the amount of the composite modified resin integrated temporary binder system, and stir for 5.5 min to make the surface of the abrasive uniformly coated with a resin liquid film. Then, add the low-temperature ceramic binder powder and stir at high speed for 9 min. Finally, add the pore-forming premix obtained in step S1 and the remaining composite modified resin integrated temporary binder system, and mix at low speed for 4.5 min to obtain a uniform blank. S3. Rotary molding: The blank is put into a rotary molding equipment and a step-by-step pressurization process is adopted. First, the pre-pressure is applied at 0.9MPa and held for 18s to release the air, and then the pressure is increased to 3.7MPa and held for 45s. The blank is then demolded to obtain the grinding wheel blank. S4. Segmented temperature and humidity controlled drying: Place the green blank into a closed humidity-controlled drying kiln and execute a four-stage drying process; S5. Four-stage oxygen pressure linkage negative pressure sintering: The dried green body is placed in a negative pressure pusher kiln and the low temperature preheating, staggered pyrolysis, ceramic sintering and stepped slow cooling processes are performed in sequence. The kiln is equipped with an oxygen probe and a negative pressure detection module to realize the interlocking control of oxygen partial pressure and negative pressure, so as to obtain a ceramic grinding wheel with large porosity.

[0046] The four-stage drying process in step S4 is as follows: the first stage is held at 42℃ and 77% relative humidity for 8.5 hours; the second stage is held at 57℃ and 62% relative humidity for 10.5 hours; the third stage is held at 72℃ and 42% relative humidity for 6.5 hours; the fourth stage is held at 92℃ with the kiln exhaust system turned on and no humidity control implemented for 4.5 hours, resulting in a green body moisture content of ≤0.3wt%. The low-temperature pre-heating process in step S5 is as follows: the kiln is evacuated to -0.045MPa, and the temperature is increased to 225℃ at a rate of 1.3℃ / min, and held for 2.7 hours to remove residual resin and moisture from the green body. The staggered pyrolysis described in step S5 specifically involves: maintaining a negative pressure of -0.035 MPa, and controlling the oxygen partial pressure and heating rate in the kiln in four stages; the first stage temperature is 260℃, the heating rate is 0.75℃ / min, and the oxygen partial pressure is 8.5%, completing the pyrolysis of walnut shell powder; the second stage temperature is 360℃, the heating rate is 0.55℃ / min, and the oxygen partial pressure is 13%, completing the pyrolysis of HDPE. Thermal decomposition; the third stage temperature is 440℃, the heating rate is 0.45℃ / min, and the oxygen partial pressure is 16%, completing the pyrolysis and gasification of PMMA microspheres; when the negative pressure is lower than the threshold of -0.03MPa, the heating rate is automatically reduced to suppress instantaneous gas generation and bubbling defects in the green body; the fourth stage temperature is 530℃, the heating rate is 1.1℃ / min, and the oxygen partial pressure is 5.5%, discharging the pore-forming agent and decomposing residual carbon; the ceramic sintering in step S5 is specifically as follows: heating to 790℃ at 1.45℃ / min, adjusting the kiln to a slight negative pressure of -0.013MPa, and holding for 2.3h; the stepped slow cooling in step S5 is specifically as follows: first cooling to 625℃ at 1.9℃ / min and holding for 1.2h; then cooling to 425℃ at 1.3℃ / min and holding for 1.7h; finally, naturally cooling to below 120℃ at a rate of ≤0.8℃ / min and exiting the kiln. Example 3

[0047] A type of porous ceramic grinding wheel is made from the following raw materials in parts by weight: 100 parts abrasive, 25 parts low-temperature ceramic binder, 18 parts surface-graded modified ternary environmentally friendly pore-forming agent, 6 parts composite modified resin integrated temporary bonding system, 0.2 parts dispersant and defoamer, and 0.2 parts auxiliary pore-forming component; the surface-graded modified ternary environmentally friendly pore-forming agent is compounded from citric acid activated walnut shell powder, plasma-etched PMMA microspheres, and maleic anhydride grafted HDPE in a mass ratio of 1:2:1.

[0048] The abrasive is green silicon carbide; the particle size of the green silicon carbide is F120; the low-temperature ceramic binder comprises the following components by weight: 72 parts of bismuth-based low-temperature glass powder, 15 parts of mullite short whiskers, 4 parts of rare earth powder, 5 parts of lithium hexafluorosilicate powder, and 4 parts of nano-zirconia powder; the nano-zirconia powder is pre-treated by wet ultrasonic dispersion to inhibit powder agglomeration; the mullite short whiskers have an aspect ratio of 40 to avoid defects caused by excessively long whiskers entanglement and agglomeration; the bismuth-based low-temperature glass powder is bismuthate-based glass powder B-5016; the diameter of the mullite short whiskers is 1.5 micrometers; the rare earth powder is HX-301 type polishing powder; the D50 of the lithium hexafluorosilicate powder is 5 μm; and the average particle size of the nano-zirconia powder is 40 nm.

[0049] The preparation method of the citric acid activated walnut shell powder includes the following steps: crushing and sieving raw walnut shells to obtain 80-mesh powder, washing with clean water and drying at 80°C, completely immersing the powder in a 5wt% citric acid-ethanol mixture prepared by anhydrous ethanol and food-grade citric acid at a solid-liquid mass ratio of 1:6, stirring and soaking in a sealed water bath at 80°C for 2 hours, then rinsing repeatedly with anhydrous ethanol to remove free citric acid, drying with hot air at 100°C, and sieving to remove lumps to obtain the finished product.

[0050] The method for preparing the plasma-etched PMMA microspheres includes the following steps: PMMA microspheres are monolayered and laid flat on a low-temperature plasma cleaning substrate under normal pressure. Etching is performed twice using a 1:1 helium-oxygen mixed gas source and 150W RF power, each etching lasting 5 minutes, with a 10-minute interval between etching and ventilation, for a total processing time of 10 minutes. After etching, the microspheres are stored at room temperature under ventilation for 30 minutes in a sealed container away from light. The PMMA microspheres are of catalog number EPRUI-CPA-1500H and are provided by Shanghai Yipurui Biotechnology Co., Ltd. The maleic anhydride-grafted HDPE is FUSABOND. TM E158 maleic anhydride-grafted HDPE.

[0051] The composite modified resin integrated temporary bonding system comprises the following components by mass percentage: 22% Illnex VISCOPOL 3324 waterborne acrylic resin, 10% Kuraray PVA-217 polyvinyl alcohol, 3% glycerol, 0.35% sodium citrate, and the balance being deionized water; the dispersing defoamer is Dow Corning defoamer DOWSIL DC-65; and the auxiliary pore-forming component is BJO-0930 phenolic hollow microspheres and silane coupling agent KH550 compounded in a mass ratio of 100:4.

[0052] A method for preparing the aforementioned porous ceramic grinding wheel includes the following steps: S1. Pretreatment of pore-forming agent by sieving: Citric acid activated walnut shell powder, plasma etched PMMA microspheres, and maleic anhydride grafted HDPE are mixed according to the formula, and large agglomerated particles are removed by passing through an 80-mesh vibrating screen. Then, it is blended with auxiliary pore-forming components to obtain surface graded modified ternary environmentally friendly pore-forming premix. S2. Gradient mixing: First, put the abrasive into a planetary mixer and premix at low speed for 2.5 min. Then, add the dispersant and defoamer and half of the amount of the composite modified resin integrated temporary binder system, and stir for 6 min to make the surface of the abrasive uniformly coated with a resin liquid film. Then, add the low-temperature ceramic binder powder and stir at high speed for 10 min. Finally, add the pore-forming premix obtained in step S1 and the remaining composite modified resin integrated temporary binder system, and mix at low speed for 5 min to obtain a uniform blank. S3. Rotary molding: The blank is put into the rotary molding equipment and a step-by-step pressurization process is adopted. First, the pre-pressure is applied at 1MPa and held for 20s to release the air, and then the pressure is increased to 4MPa and held for 50s. The grinding wheel blank is then demolded. S4. Segmented temperature and humidity controlled drying: Place the green blank of the grinding wheel into a closed humidity-controlled drying kiln and execute a four-stage drying process; S5. Four-stage oxygen pressure linkage negative pressure sintering: The dried green body is placed in a negative pressure pusher kiln and the low temperature preheating, staggered pyrolysis, ceramic sintering and stepped slow cooling processes are performed in sequence. The kiln is equipped with an oxygen probe and a negative pressure detection module to realize the interlocking control of oxygen partial pressure and negative pressure, so as to obtain a ceramic grinding wheel with large porosity.

[0053] The four-stage drying process in step S4 is as follows: the first stage is at a temperature of 43℃ and a relative humidity of 78%, held for 9 hours; the second stage is at a temperature of 58℃ and a relative humidity of 63%, held for 11 hours; the third stage is at a temperature of 73℃ and a relative humidity of 43%, held for 7 hours; the fourth stage is at a temperature of 93℃, with exhaust ventilation in the kiln turned on and no humidity control, held for 5 hours, and the moisture content of the green body after drying is ≤0.3wt%; the low-temperature pre-heating process in step S5 is as follows: the negative pressure in the kiln is reduced to -0.05MPa, the temperature is increased to 230℃ at a rate of 1.35℃ / min, and held for 3 hours to remove residual resin and moisture from the green body; The staggered pyrolysis described in step S5 specifically involves: maintaining a negative pressure of -0.04 MPa, and controlling the oxygen partial pressure and heating rate in the kiln in four stages; the first stage temperature is 300℃, the heating rate is 0.8℃ / min, and the oxygen partial pressure is 9%, completing the pyrolysis of walnut shell powder; the second stage temperature is 390℃, the heating rate is 0.6℃ / min, and the oxygen partial pressure is 13.5%, completing the pyrolysis of HDPE. Thermal decomposition; the third stage temperature is 470℃, the heating rate is 0.5℃ / min, and the oxygen partial pressure is 16.5%, completing the pyrolysis and gasification of PMMA microspheres; when the negative pressure is lower than the threshold of -0.03MPa, the heating rate is automatically reduced to suppress instantaneous gas generation and bubbling defects in the green body; the fourth stage temperature is 550℃, the heating rate is 1.1℃ / min, and the oxygen partial pressure is 6%, discharging the pore-forming agent and decomposing residual carbon; the ceramic sintering in step S5 is specifically as follows: heating to 800℃ at 1.5℃ / min, adjusting the kiln to a slight negative pressure of -0.015MPa, and holding for 2.5h; the stepped slow cooling in step S5 is specifically as follows: first cooling to 630℃ at 2℃ / min and holding for 1.3h; then cooling to 430℃ at 1.35℃ / min and holding for 1.8h; finally, naturally cooling to below 120℃ at a rate of ≤0.8℃ / min and exiting the kiln.

[0054] Example 4 A ceramic grinding wheel with large pores is made from the following raw materials in parts by weight: 100 parts abrasive, 27 parts low-temperature ceramic binder, 21 parts surface-graded modified ternary environmentally friendly pore-forming agent, 7.5 parts composite modified resin integrated temporary bonding system, 0.25 parts dispersant and defoamer, and 0.25 parts auxiliary pore-forming components; the surface-graded modified ternary environmentally friendly pore-forming agent is compounded from citric acid activated walnut shell powder, plasma-etched PMMA microspheres, and maleic anhydride grafted HDPE in a mass ratio of 1:2:1.1.

[0055] The abrasive is a compound of white fused alumina, brown fused alumina, and green silicon carbide in a mass ratio of 1:1:2 (bismuth); the white fused alumina has a particle size of F80; the brown fused alumina has a particle size of F100; and the green silicon carbide has a particle size of F120. The low-temperature ceramic binder comprises the following components by weight: 73 parts bismuth-based low-temperature glass powder, 15.5 parts mullite short whiskers, 4.5 parts rare earth powder, 5.5 parts lithium hexafluorosilicate powder, and 4.5 parts nano-zirconia powder. The nano-zirconia powder is pre-treated with wet ultrasonic dispersion to inhibit powder agglomeration; the mullite short whiskers have an aspect ratio of 50 to avoid defects caused by excessively long whiskers entanglement and agglomeration; the bismuth-based low-temperature glass powder is bismuthate-based glass powder B-5016; the diameter of the mullite short whiskers is 2.5 micrometers; the rare earth powder is HX-301 type polishing powder; the D50 of the lithium hexafluorosilicate powder is 7 μm; and the average particle size of the nano-zirconia powder is 45 nm.

[0056] The preparation method of the citric acid activated walnut shell powder includes the following steps: crushing and sieving raw walnut shells to obtain 95-mesh powder, washing with water and drying at 81°C, completely immersing the powder in a 5wt% citric acid-ethanol mixture prepared by anhydrous ethanol and food-grade citric acid at a solid-liquid mass ratio of 1:6, stirring and soaking in a sealed water bath at 81°C for 2.1 hours, then rinsing repeatedly with anhydrous ethanol to remove free citric acid, drying with hot air at 101°C, and sieving to remove lumps to obtain the finished product.

[0057] The method for preparing the plasma-etched PMMA microspheres includes the following steps: PMMA microspheres are monolayered and laid flat on a low-temperature plasma cleaning substrate under normal pressure. Etching is performed twice using a helium-oxygen mixed gas source with a volume ratio of 1:1 and a 150W radio frequency power, each etching lasting 5 minutes, with a 10-minute interval between etching and ventilation. The total processing time is 10 minutes. After etching, the microspheres are stored at room temperature under ventilation for 30 minutes in a sealed container away from light. The PMMA microspheres are EPRUI-CPA-1500H and are provided by Shanghai Yipurui Biotechnology Co., Ltd. The maleic anhydride-grafted HDPE is FUSABONDTME158 maleic anhydride-grafted HDPE.

[0058] The composite modified resin integrated temporary bonding system comprises the following components by mass percentage: 22.5% Illex VISCOPOL 3324 waterborne acrylic resin, 10.5% Kuraray PVA-217 polyvinyl alcohol, 3.5% glycerin, 0.45% sodium citrate, and the balance being deionized water; the dispersing defoamer is Dow Corning defoamer DOWSIL DC-65; and the auxiliary pore-forming component is BJO-0930 phenolic hollow microspheres and silane coupling agent KH550 compounded in a mass ratio of 100:4.5.

[0059] A method for preparing the aforementioned porous ceramic grinding wheel includes the following steps: S1. Pretreatment of pore-forming agent by sieving: Citric acid activated walnut shell powder, plasma etched PMMA microspheres, and maleic anhydride grafted HDPE are mixed according to the formula, and large agglomerated particles are removed by passing through an 80-mesh vibrating screen. Then, it is blended with auxiliary pore-forming components to obtain surface graded modified ternary environmentally friendly pore-forming premix. S2. Gradient mixing: First, put the abrasive into a planetary mixer and premix at low speed for 2.8 min. Then, add the dispersant and defoamer and half of the amount of the composite modified resin integrated temporary binder system, and stir for 6.5 min to make the surface of the abrasive uniformly coated with a resin liquid film. Then, add the low-temperature ceramic binder powder and stir at high speed for 11 min. Finally, add the pore-forming premix obtained in step S1 and the remaining composite modified resin integrated temporary binder system, and mix at low speed for 5.5 min to obtain a uniform blank. S3. Rotary molding: The blank is put into a rotary molding equipment and a step-by-step pressurization process is adopted. First, the pre-pressure is applied at 1.1MPa and held for 24s to release the air, and then the pressure is increased to 4.3MPa and held for 55s. The blank is then demolded to obtain the grinding wheel blank. S4. Segmented temperature and humidity controlled drying: Place the green blank into a closed humidity-controlled drying kiln and execute a four-stage drying process; S5. Four-stage oxygen pressure linkage negative pressure sintering: The dried green body is placed in a negative pressure pusher kiln and the low temperature preheating, staggered pyrolysis, ceramic sintering and stepped slow cooling processes are performed in sequence. The kiln is equipped with an oxygen probe and a negative pressure detection module to realize the interlocking control of oxygen partial pressure and negative pressure, so as to obtain a ceramic grinding wheel with large porosity.

[0060] The four-stage drying process in step S4 is as follows: the first stage is at a temperature of 44℃ and a relative humidity of 79%, held for 9.5 hours; the second stage is at a temperature of 59℃ and a relative humidity of 64%, held for 11.5 hours; the third stage is at a temperature of 74℃ and a relative humidity of 44%, held for 7.5 hours; the fourth stage is at a temperature of 94℃, with exhaust ventilation in the kiln turned on and no humidity control, held for 5.5 hours, and the moisture content of the green body after drying is ≤0.3wt%; the low-temperature pre-heating process in step S5 is as follows: the kiln is evacuated to a negative pressure of -0.055MPa, the temperature is increased to 235℃ at a rate of 1.4℃ / min, and held for 3.3 hours to remove residual resin and moisture from the green body; The staggered pyrolysis described in step S5 specifically involves: maintaining a negative pressure of -0.045 MPa, and controlling the oxygen partial pressure and heating rate in the kiln in four stages; the first stage temperature is 330℃, the heating rate is 0.85℃ / min, and the oxygen partial pressure is 9.5%, completing the pyrolysis of walnut shell powder; the second stage temperature is 410℃, the heating rate is 0.65℃ / min, and the oxygen partial pressure is 14.5%, completing the pyrolysis of HDPE. Thermal decomposition; the third stage temperature is 505℃, the heating rate is 0.55℃ / min, and the oxygen partial pressure is 17.5%, completing the pyrolysis and gasification of PMMA microspheres; when the negative pressure is lower than the threshold of -0.03MPa, the heating rate is automatically reduced to suppress instantaneous gas generation and bubbling defects in the green body; the fourth stage temperature is 570℃, the heating rate is 1.2℃ / min, and the oxygen partial pressure is 6.5%, discharging the pore-forming agent and decomposing residual carbon; the ceramic sintering in step S5 is specifically as follows: heating to 810℃ at 1.55℃ / min, adjusting the kiln to a slight negative pressure of -0.018MPa, and holding for 2.8h; the stepped slow cooling in step S5 is specifically as follows: first cooling to 635℃ at 2.1℃ / min and holding for 1.4h; then cooling to 438℃ at 1.45℃ / min and holding for 1.9h; finally, naturally cooling to below 120℃ at a rate of ≤0.8℃ / min and exiting the kiln.

[0061] Example 5 A ceramic grinding wheel with large pores is made from the following raw materials in parts by weight: 100 parts abrasive, 28 parts low-temperature ceramic binder, 22 parts surface-graded modified ternary environmentally friendly pore-forming agent, 8 parts composite modified resin integrated temporary bonding system, 0.3 parts dispersant and defoamer, and 0.3 parts auxiliary pore-forming component; the surface-graded modified ternary environmentally friendly pore-forming agent is compounded from citric acid activated walnut shell powder, plasma-etched PMMA microspheres, and maleic anhydride grafted HDPE in a mass ratio of 1:2:1.2.

[0062] The abrasive is white fused alumina; the particle size of the white fused alumina is F80; the low-temperature ceramic binder comprises the following components by weight: 74 parts of bismuth-based low-temperature glass powder, 16 parts of mullite short whiskers, 5 parts of rare earth powder, 6 parts of lithium hexafluorosilicate powder, and 5 parts of nano-zirconia powder; the nano-zirconia powder is pre-treated by wet ultrasonic dispersion to inhibit powder agglomeration; the mullite short whiskers have an aspect ratio of 60 to avoid defects caused by excessively long whiskers entanglement and agglomeration; the bismuth-based low-temperature glass powder is bismuthate-based glass powder B-5016; the diameter of the mullite short whiskers is 3 micrometers; the rare earth powder is HX-301 type polishing powder; the D50 of the lithium hexafluorosilicate powder is 8 μm; and the average particle size of the nano-zirconia powder is 50 nm.

[0063] The preparation method of the citric acid activated walnut shell powder includes the following steps: crushing and sieving raw walnut shells to obtain 100-mesh powder, washing with water and drying at 82°C, completely immersing the powder in a 5wt% citric acid-ethanol mixture prepared by anhydrous ethanol and food-grade citric acid at a solid-liquid mass ratio of 1:6, stirring and soaking in a sealed water bath at 82°C for 2.2 hours, then rinsing repeatedly with anhydrous ethanol to remove free citric acid, drying with hot air at 102°C, and sieving to remove lumps to obtain the finished product.

[0064] The method for preparing the plasma-etched PMMA microspheres includes the following steps: PMMA microspheres are monolayered and laid flat on a low-temperature plasma cleaning substrate under normal pressure. Etching is performed twice using a 1:1 helium-oxygen mixed gas source and 150W RF power, each etching lasting 5 minutes, with a 10-minute interval between etching and ventilation, for a total processing time of 10 minutes. After etching, the microspheres are stored at room temperature under ventilation for 30 minutes in a sealed container away from light. The PMMA microspheres are of catalog number EPRUI-CPA-1500H and are provided by Shanghai Yipurui Biotechnology Co., Ltd. The maleic anhydride-grafted HDPE is FUSABOND. TM E158 maleic anhydride-grafted HDPE.

[0065] The composite modified resin integrated temporary bonding system comprises the following components by mass percentage: 23% Illnex VISCOPOL 3324 waterborne acrylic resin, 11% Kuraray PVA-217 polyvinyl alcohol, 4% glycerol, 0.5% sodium citrate, and the balance being deionized water; the dispersing defoamer is Dow Corning defoamer DOWSIL DC-65; and the auxiliary pore-forming component is BJO-0930 phenolic hollow microspheres and silane coupling agent KH550 compounded in a mass ratio of 100:5.

[0066] A method for preparing the aforementioned porous ceramic grinding wheel includes the following steps: S1. Pretreatment of pore-forming agent by sieving: Citric acid activated walnut shell powder, plasma etched PMMA microspheres, and maleic anhydride grafted HDPE are mixed according to the formula, and large agglomerated particles are removed by passing through an 80-mesh vibrating screen. Then, it is blended with auxiliary pore-forming components to obtain surface graded modified ternary environmentally friendly pore-forming premix. S2. Gradient mixing: First, put the abrasive into a planetary mixer and premix at low speed for 3 minutes. Then, add the dispersant and defoamer and half of the amount of the composite modified resin integrated temporary binder system, and stir for 7 minutes to make the surface of the abrasive uniformly coated with a resin liquid film. Then, add the low-temperature ceramic binder powder and stir at high speed for 12 minutes. Finally, add the pore-forming premix obtained in step S1 and the remaining composite modified resin integrated temporary binder system, and mix at low speed for 6 minutes to obtain a uniform blank. S3. Rotary molding: The blank is put into a rotary molding equipment and a step-by-step pressurization process is adopted. First, the pre-pressure is applied at 1.2MPa and held for 25s to release the air, and then the pressure is increased to 4.5MPa and held for 60s. The blank is then demolded to obtain the grinding wheel blank. S4. Segmented temperature and humidity controlled drying: Place the green blank of the grinding wheel into a closed humidity-controlled drying kiln and execute a four-stage drying process; S5. Four-stage oxygen pressure linkage negative pressure sintering: The dried green body is placed in a negative pressure pusher kiln and the low temperature preheating, staggered pyrolysis, ceramic sintering and stepped slow cooling processes are performed in sequence. The kiln is equipped with an oxygen probe and a negative pressure detection module to realize the interlocking control of oxygen partial pressure and negative pressure, so as to obtain a ceramic grinding wheel with large porosity.

[0067] The four-stage drying process in step S4 is as follows: the first stage is at a temperature of 45℃ and a relative humidity of 80%, held for 10 hours; the second stage is at a temperature of 60℃ and a relative humidity of 65%, held for 12 hours; the third stage is at a temperature of 75℃ and a relative humidity of 45%, held for 8 hours; the fourth stage is at a temperature of 95℃, with exhaust ventilation in the kiln turned on and no humidity control, held for 6 hours, and the moisture content of the green body after drying is ≤0.3wt%; the low-temperature pre-heating process in step S5 is as follows: the kiln is evacuated to a negative pressure of -0.06MPa, the temperature is increased to 240℃ at a rate of 1.5℃ / min, and held for 3.5 hours to remove residual resin and moisture from the green body; The staggered pyrolysis described in step S5 is as follows: maintaining a negative pressure of -0.05 MPa, the oxygen partial pressure and heating rate in the kiln are controlled in four stages; the first stage temperature is 340℃, the heating rate is 0.9℃ / min, and the oxygen partial pressure is 10%, completing the pyrolysis of walnut shell powder; the second stage temperature is 420℃, the heating rate is 0.7℃ / min, and the oxygen partial pressure is 15%, completing the thermal decomposition of HDPE; the third stage temperature is 510℃, the heating rate is 0.6℃ / min, and the oxygen partial pressure is 18%, completing the pyrolysis and gasification of PMMA microspheres; when the negative pressure is lower than the threshold of -0.03 MPa, the heating rate is automatically reduced to suppress instantaneous gas generation and the resulting bubbling defects in the green body; the fourth stage temperature is 580℃, the heating rate is 1.2℃ / min, and the oxygen partial pressure is 7%, discharging the pore-forming agent and decomposing residual carbon.

[0068] The ceramic sintering described in step S5 is as follows: the temperature is increased to 820℃ at a rate of 1.6℃ / min, the pressure inside the kiln is adjusted to a slight negative pressure of -0.02MPa, and the temperature is held for 3 hours. The stepped slow cooling described in step S5 is as follows: first, the temperature is decreased to 640℃ at a rate of 2.2℃ / min and held for 1.5 hours; then, the temperature is decreased to 440℃ at a rate of 1.5℃ / min and held for 2 hours; finally, the temperature is naturally decreased to below 120℃ at a rate of ≤0.8℃ / min before the ceramic is removed from the kiln.

[0069] Comparative Example 1 A porous ceramic grinding wheel and its preparation method are basically the same as in Example 5, except that no auxiliary pore-forming components are added.

[0070] Comparative Example 2 A porous ceramic grinding wheel and its preparation method are basically the same as in Example 5, except that an equal amount of citric acid-activated walnut shell powder is used instead of plasma-etched PMMA microspheres.

[0071] Comparative Example 3 A porous ceramic grinding wheel and its preparation method are basically the same as in Example 5, except that an equal amount of rare earth powder is used instead of lithium hexafluorosilicate powder.

[0072] Comparative Example 4 A porous ceramic grinding wheel and its preparation method are basically the same as in Example 5, except that an equal amount of lithium hexafluorosilicate powder is used instead of rare earth powder.

[0073] Comparative Example 5 A porous ceramic grinding wheel and its preparation method are basically the same as in Example 5, except that an equal amount of plasma-etched PMMA microspheres are used instead of citric acid-activated walnut shell powder.

[0074] To further illustrate the unexpected positive technical effects achieved by the atmospheric porous ceramic grinding wheel in the embodiments of the present invention, relevant performance tests were conducted on the products involved in Example 5 and Comparative Examples 1-5. The test results are shown in Table 1, and the test methods are as follows: (1) Porosity test: Referring to GB / T 1966-1996 "Test method for apparent porosity and bulk density of porous ceramics", the sintered ceramic grinding wheel was cut into 10mm×10mm×10mm standard samples. The boiling method was used to saturate and absorb water. The dry weight, wet weight and floating weight were weighed respectively. The apparent porosity was calculated by Archimedes' principle. The arithmetic mean of 5 parallel samples in each group was taken to ensure the accuracy of the results.

[0075] (2) Bending strength test: Referring to GB / T 6569-2006 "Test method for bending strength of fine ceramics", the grinding wheel was processed into a strip specimen of 50mm×10mm×5mm. The three-point bending test mode was adopted, the support span was 40mm, the loading rate was 5mm / min, and the specimen was loaded until it broke through the universal testing machine. The breaking load was recorded and the bending strength was calculated. Six specimens were tested in each group, and the average value was taken after removing the large discrete values.

[0076] (3) Sintering linear shrinkage rate test: Refer to QB / T 1548-2015 "Method for determining the linear shrinkage rate of ceramic blanks and clay". During the greening stage, the length and width reference dimensions are measured with a vernier caliper with an accuracy of 0.02mm. After sintering and cooling to room temperature, the corresponding positions are measured again. The relative change rate of dimensions before and after sintering is calculated. Five samples are prepared with the same formula, and the transverse and longitudinal shrinkage rates are measured respectively. The arithmetic mean is taken as the final result.

[0077] (4) Evaluation of porosity: The cross-section of the grinding wheel sample was metallographically polished. Five random fields of view were selected in each of the three height regions of the sample (upper, middle and lower) using an optical microscope to take micrographs. The distribution and proportion of pore diameter in each field of view were statistically analyzed using image analysis software. The uniformity was evaluated by calculating the dispersion coefficient of pore parameters in different fields of view. The smaller the dispersion coefficient, the more uniform the pore distribution.

[0078] (5) Rotational explosion safety test of grinding wheel: Refer to GB / T 2493-2017 "Rotational test method of grinding wheel", clamp the finished ceramic grinding wheel in the rotational testing machine, run it at 1.5 times the rated working speed for 2 minutes, observe whether cracks, chipping or explosion occur, record the ultimate explosion speed when the grinding wheel is destroyed, and evaluate its safety performance.

[0079] Table 1 Performance test results of atmospheric porous ceramic grinding wheels

[0080] As shown in Table 1, the atmospheric porous ceramic grinding wheel prepared in Example 5 of this invention exhibits the best overall performance. Compared to Comparative Example 1 (without auxiliary pore-forming components), Comparative Example 2 (using walnut shell powder instead of plasma-etched PMMA microspheres), Comparative Example 3 (using rare earth powder instead of lithium hexafluorosilicate), Comparative Example 4 (using lithium hexafluorosilicate instead of rare earth powder), and Comparative Example 5 (using citric acid-activated walnut shell powder instead of PMMA microspheres), it maintains a high apparent porosity of 47.2% while retaining an excellent flexural strength of 23.6 MPa. It also exhibits moderate sintering linear shrinkage, a low porosity dispersion coefficient of 0.055, the best porosity uniformity, and an ultimate bursting speed of 2.42 times the rated speed, demonstrating outstanding dimensional stability and safety. Comparative Example 2, using only a biomass pore-forming agent, while exhibiting a slightly higher porosity, produced numerous irregular interconnected pores, compromising the matrix integrity and resulting in the worst mechanical and safety performance. Comparative Example 5... Using PMMA microspheres alone for pore formation results in superior pore regularity and mechanical properties compared to other conventional comparative examples. However, the lack of a hierarchical pore structure leads to a low porosity, failing to achieve high porosity adaptability. Comparative Example 1 lacks auxiliary pore-forming modification components, resulting in insufficient porosity and increased interface defects. Comparative Examples 3 and 4 disrupt the synergistic fluxing and toughening system of lithium hexafluorosilicate and rare earth powder, exhibiting problems such as insufficient sintering densification and reduced matrix toughening effect. All performance aspects are inferior to Example 5. This fully demonstrates that the present invention employs a ternary hierarchical pore-forming system composed of citric acid-activated walnut shell powder, plasma-etched PMMA microspheres, and maleic anhydride-grafted HDPE, combined with a suitable low-temperature ceramic binder. Through hierarchical pore structure control and synergistic modification of the matrix interface, it effectively balances the porosity, pore uniformity, dimensional stability, mechanical strength, and burst safety of the grinding wheel, exhibiting excellent comprehensive performance and significant technical advantages.

[0081] The above embodiments are only for illustrating the technical concept and features of the present invention. Their purpose is to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be used to limit the scope of protection of the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A ceramic grinding wheel with large porosity, characterized in that, It is made from the following raw materials in parts by weight: 100 parts abrasive, 20-28 parts low-temperature ceramic binder, 10-22 parts surface-graded modified ternary environmentally friendly pore-forming agent, 4-8 parts composite modified resin integrated temporary bonding system, 0.1-0.3 parts dispersant and defoamer, and 0.1-0.3 parts auxiliary pore-forming components; the surface-graded modified ternary environmentally friendly pore-forming agent is compounded from citric acid activated walnut shell powder, plasma-etched PMMA microspheres, and maleic anhydride grafted HDPE in a mass ratio of 1:2:(0.8-1.2).

2. The atmospheric porous ceramic grinding wheel according to claim 1, characterized in that, The abrasive is at least one of white fused alumina, brown fused alumina, and green silicon carbide; the white fused alumina has a particle size of F80; the brown fused alumina has a particle size of F100; and the green silicon carbide has a particle size of F120.

3. The atmospheric porous ceramic grinding wheel according to claim 1, characterized in that, The low-temperature ceramic binder comprises the following components by weight: 70-74 parts bismuth-based low-temperature glass powder, 14-16 parts mullite short whiskers, 3-5 parts rare earth powder, 4-6 parts lithium hexafluorosilicate powder, and 3-5 parts nano-zirconia powder; the nano-zirconia powder is pre-treated by wet ultrasonic dispersion to inhibit powder agglomeration; the mullite short whiskers have an aspect ratio of 20-60 to avoid defects caused by excessively long whiskers entanglement and agglomeration; the bismuth-based low-temperature glass powder is bismuthate-based glass powder B-5016; the diameter of the mullite short whiskers is 0.2-3 micrometers; the rare earth powder is HX-301 type polishing powder; the D50 of the lithium hexafluorosilicate powder is 2-8 μm; and the average particle size of the nano-zirconia powder is 30-50 nm.

4. The atmospheric porous ceramic grinding wheel according to claim 1, characterized in that, The preparation method of the citric acid activated walnut shell powder includes the following steps: crushing and sieving raw walnut shells to obtain 60-100 mesh powder, washing with clean water and drying at 78-82℃, completely immersing the powder in a 5wt% citric acid-ethanol mixture prepared by anhydrous ethanol and food-grade citric acid at a solid-liquid mass ratio of 1:6, stirring and soaking in a closed water bath at 78-82℃ for 1.8-2.2 hours, then rinsing repeatedly with anhydrous ethanol to remove free citric acid, drying with hot air at 98-102℃, and sieving to remove lumps to obtain the finished product.

5. The atmospheric porous ceramic grinding wheel according to claim 1, characterized in that, The method for preparing the plasma-etched PMMA microspheres includes the following steps: PMMA microspheres are monolayered and laid flat on a low-temperature plasma cleaning substrate under normal pressure. Etching is performed twice using a helium-oxygen mixed gas source with a volume ratio of 1:1 and a radio frequency power of 150W, each time for 5 minutes, with an intermediate 10-minute ventilated resting period, for a total processing time of 10 minutes. After etching, the microspheres are stored at room temperature under ventilation for 30 minutes in a sealed container away from light. The PMMA microspheres have the product number EPRUI-CPA-1500H and are provided by Shanghai EPRUI Biotechnology Co., Ltd.

6. The atmospheric porous ceramic grinding wheel according to claim 1, characterized in that, The maleic anhydride-grafted HDPE is FUSABOND. TM E158 maleic anhydride-grafted HDPE; the composite modified resin integrated temporary bonding system comprises the following components by mass percentage: 21-23% Illex VISCOPOL 3324 waterborne acrylic resin, 9-11% Kuraray PVA-217 polyvinyl alcohol, 2-4% glycerol, 0.2-0.5% sodium citrate, and the balance being deionized water.

7. The atmospheric porous ceramic grinding wheel according to claim 1, characterized in that, The dispersing defoamer is Dow Corning defoamer DOWSIL DC-65; the auxiliary pore-forming component is BJO-0930 phenolic hollow microspheres and silane coupling agent KH550 compounded in a mass ratio of 100:(3-5).

8. A method for preparing a porous ceramic grinding wheel according to any one of claims 1-7, characterized in that, Includes the following steps: S1. Pretreatment of pore-forming agent by sieving: Citric acid activated walnut shell powder, plasma etched PMMA microspheres, and maleic anhydride grafted HDPE are mixed according to the formula, and large agglomerated particles are removed by passing through an 80-mesh vibrating screen. Then, it is blended with auxiliary pore-forming components to obtain surface graded modified ternary environmentally friendly pore-forming premix. S2. Gradient mixing: First, put the abrasive into a planetary mixer and premix at low speed for 2-3 minutes. Then, add the dispersant and defoamer and half of the amount of the composite modified resin integrated temporary bonding system, and stir for 5-7 minutes to make the surface of the abrasive uniformly coated with a resin liquid film. Add low-temperature ceramic binder powder and stir at high speed for 8-12 minutes; finally add the pore-forming premix obtained in step S1 and the remaining composite modified resin integrated temporary bonding system, and mix at low speed for 4-6 minutes to obtain a uniform blank. S3. Rotary molding: The blank is put into a rotary molding equipment and a step-by-step pressurization process is adopted. First, the pre-pressure is applied at 0.8-1.2MPa and held for 15-25s to release the air. Then, the pressure is increased to 3.5-4.5MPa and held for 40-60s. The blank is demolded to obtain the grinding wheel blank. S4. Segmented temperature and humidity controlled drying: Place the green blank of the grinding wheel into a closed humidity-controlled drying kiln and execute a four-stage drying process; S5. Four-stage oxygen pressure linkage negative pressure sintering: The dried green body is placed in a negative pressure pusher kiln and the low temperature preheating, staggered pyrolysis, ceramic sintering and stepped slow cooling processes are performed in sequence. The kiln is equipped with an oxygen probe and a negative pressure detection module to realize the interlocking control of oxygen partial pressure and negative pressure, so as to obtain a ceramic grinding wheel with large porosity.

9. The method for preparing a porous ceramic grinding wheel according to claim 8, characterized in that, The four-stage drying process in step S4 is as follows: the first stage is at a temperature of 40-45℃ and a relative humidity of 75-80%, and is held for 8-10 hours; the second stage is at a temperature of 55-60℃ and a relative humidity of 60-65%, and is held for 10-12 hours; the third stage is at a temperature of 70-75℃ and a relative humidity of 40-45%, and is held for 6-8 hours; the fourth stage is at a temperature of 90-95℃, with exhaust ventilation in the kiln turned on and no humidity control, and is held for 4-6 hours. After drying, the moisture content of the green body is ≤0.3wt%. The low-temperature pre-heating process in step S5 is as follows: the kiln is evacuated to a negative pressure of -0.04~-0.06MPa, and the temperature is increased to 220-240℃ at a rate of 1.2-1.5℃ / min, and held for 2.5-3.5 hours to remove residual resin and moisture from the green body.

10. The method for preparing a porous ceramic grinding wheel according to claim 8, characterized in that, The staggered pyrolysis described in step S5 specifically involves maintaining a negative pressure of -0.03 to -0.05 MPa and controlling the oxygen partial pressure and heating rate in the kiln in four stages. The first stage involves a temperature of 240-340℃, a heating rate of 0.7-0.9℃ / min, and an oxygen partial pressure of 8-10%, completing the pyrolysis of walnut shell powder. The second stage involves a temperature of 340-420℃, a heating rate of 0.5-0.7℃ / min, and an oxygen partial pressure of 12-15%, completing the pyrolysis of HDPE. Thermal decomposition; the third stage temperature is 420-510℃, the heating rate is 0.4-0.6℃ / min, and the oxygen partial pressure is 15-18%, completing the pyrolysis and gasification of PMMA microspheres; when the negative pressure is lower than the -0.03MPa threshold, the heating rate is automatically reduced to suppress instantaneous gas generation and bubbling defects in the green body; the fourth stage temperature is 510-580℃, the heating rate is 1.0-1.2℃ / min, and the oxygen partial pressure is 5-7%, discharging the pore-forming agent and decomposing residual carbon; the ceramic sintering described in step S5 specifically involves: The temperature is increased to 780-820℃ at a rate of 1.4-1.6℃ / min, and the kiln is adjusted to a slight negative pressure of -0.01~-0.02MPa, and held for 2-3 hours. The step-by-step slow cooling in step S5 is as follows: first, the temperature is reduced to 620-640℃ at a rate of 1.8-2.2℃ / min and held for 1-1.5 hours; then, the temperature is reduced to 420-440℃ at a rate of 1.2-1.5℃ / min and held for 1.5-2 hours; finally, the temperature is naturally reduced to below 120℃ at a rate of ≤0.8℃ / min before exiting the kiln.

Citation Information

Patent Citations

  • Low-density large-pore ceramic grinding wheel and preparation method thereof

    CN112677059A